2015
DOI: 10.1590/0100-67622015000100008
|View full text |Cite
|
Sign up to set email alerts
|

INTERAÇÃO GENÓTIPOS X AMBIENTES PARA PRODUTIVIDADE DE CLONES DE Eucalyptus L'Hér. NO ESTADO DO RIO GRANDE DO SUL

Abstract: Este trabalho objetivou estudar a interação genótipos em ambientes de clones de Eucalyptus em quatro ambientes do Estado do Rio Grande do Sul. Os ensaios foram conduzidos nas áreas da empresa CMPC Celulose Riograndense, nos Municípios de Minas do Leão (Horto Florestal Cambará), Encruzilhada do Sul (Horto Florestal Capivara), Dom Feliciano (Horto Florestal Fortaleza) e Vila Nova do Sul (Horto Florestal São João). No ano 2007, foi implantada uma rede de testes clonais com 864 clones de Eucalyptus, pertencentes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 6 publications
5
14
0
5
Order By: Relevance
“…Similar results were found in the work by Santos et al (2015), for Eucalyptus clones in Rio Grande do Sul. According to Resende (2002), only when the genetic correlation value between locations is over 70% it is possible to carry out a single improvement population.…”
Section: Resultssupporting
confidence: 91%
“…Similar results were found in the work by Santos et al (2015), for Eucalyptus clones in Rio Grande do Sul. According to Resende (2002), only when the genetic correlation value between locations is over 70% it is possible to carry out a single improvement population.…”
Section: Resultssupporting
confidence: 91%
“…The analysis of the heritability coefficients within families showed that they were much lower than the heritability based on a family average. Other studies have found similar results in clones of Eucalyptus L'Hér (Santos et al 2015) and Eucalyptus pellita F. Muell (Hung et al 2015), which agrees with this work, since both species are perennial. This result allows inferring that the selection based on the average of the families can be more efficient than within families.…”
Section: I2supporting
confidence: 92%
“…These can be considered satisfactory values for experiments with perennial species (Verardi et al 2011;Santos et al 2015) since they indicate good experimental precision.…”
Section: I2mentioning
confidence: 79%
“…Distintos autores reportam em estudos de interação G x A em eucalipto (RAYMOND et al, 1997;MUNERI;RAYMOND, 2000;OSORIO et al, 2001;HARDNER et al, 2010;SANTOS et al, 2015) que determinar a importância prática e magnitude da interação G x A é crítico para o delineamento de programas de melhoramento e para a tomada de decisões no estabelecimento dos plantios. Além disso, quando há interação G x A significativa é fundamental a separação de áreas específicas para recomendação, plantio ou teste de determinados materiais genéticos.…”
Section: Capivaraunclassified